Potentiometric determination of the total acidity and concentration of citric acid in wines; Journal of Analytical Chemistry; Vol. 66, iss. 9 - Zakharova E. A. Elsa Arminana; Moskaleva M. L.; Akeneev Yu. A. Yuriy Anvarovich; Moiseeva E. S. Evgeniya Sergeevna; Slepchenko G. B. Galina Borisovna; Pikula N. P. Nina Pavlovna (2011, 2011)
Title screen